Study the relationship between Algeria society and Requirements for management creativity - Benikhlef, Zohra; Abbas, Nawal (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aims to define the impact of the popular nature of Algerian society on administrative creativity, by focusing on three basic components of the popular nature of the country that were considered as independent variables in the research: The popular character in economic dealings, the coexistence of corruption with society, and finally the consolidation of the policy of social peace ,as for the dependent variable, it was specifically represented in the requirements of administrative innovation, and the descriptive approach was applied through theoretical rooting as a description of the study variables, in addition to the deductive analytical method through a social survey. Purpose Design a written questionnaire that includes 16 statements dealing with independent variables and 9 statements dealing with the dependent variable. Distributed to a random sample (25 of males and females, at different educational levels and administrative ranks) of administrators at the Faculty of Economics, University of Tlemcen, Algeria, divided into 5 administrative departments. The most important results were to prove the strong impact of the populist nature of Algerian society, with all its harbingers, on activating the innovation process. The study concluded that it is necessary to get rid of the dependence of economic transactions in general to dictates and social pressures in order to liberate innovation at all levels.
Keywords: Administrative Creativity; Algerian Society; Promoting Social Peace; Promoting Patronage